Synthesizing auroral substorm processes based on magnetosphere-ionosphere electric currents - Akasofu, Syun-Ichi; Lui, A. T. Y.; Lee, Lou-Chuang (Frontiers in Astronomy and Space Sciences, 2025)
A synthesis of various processes associated with auroral substorms is attempted by considering medium intensity substorms. In this paper, we consider that the magnetosphere-ionosphere system is an electric current system. When the solar wind-magnetosphere dynamo power starts to increase above 1011 W, the current cannot flow in a quiet (low conductive) ionosphere, so that the current is initially blocked, causing energy accumulation of about 1016 J and inflation of the inner magnetosphere during the growth phase. This initial anomaly is removed by the development of a specific instability of the cross-tail current and subsequent disruption, causing deflation and the so-called dipolarization in the inner magnetosphere. These processes result in the development of the earthward electric field, which generates a new current system of sheet field-aligned current together with the double layer, greatly increasing the ionization of the ionosphere and establishing the expansion phase, the sudden brightening of an arc. This sequence of processes allows finally the disrupted cross-tail current to flow in the ionosphere (the auroral electrojet), dissipating the accumulated magnetic energy manifested by auroral substorms, so that the whole system can function finally like a normal current system, the recovery phase.